PSF hollow fiber membrane fabricated from PSF–HBPE–PEG400–DMAc dope solutions via reverse thermally induced phase separation (RTIPS) process. (1st December 2015) - Zhao, Long-Bao; Liu, Min; Xu, Zhen-Liang; Wei, Yong-Ming; Xu, Min-Xian
Abstract: Hyperbranched polyesters (HBPEs) based on 2, 2-bis(methylol)propionic acid (bis-MPA) was used as an additive to prepare polysulfone (PSf) hollow fiber membranes while the PSf–HBPE–PEG400–DMAc dope solutions were low critical solution temperature (LCST) membrane-forming systems. When the temperature of the coagulation bath was lower than the cloud point, the membrane formation process was the NIPS process, and the finger-like structure could be found in the membranes. The hydrophilicity, porosity, pure water flux, mean effective pore size and breaking strength of these prepared membranes increased with increasing the HBPE content. On the other hand, when the temperature of the coagulation bath reached the cloud point, the membrane formation process was changed to the reverse thermally induced phase separation (RTIPS) process. In these membranes, the finger-like structure was replaced by the sponge-like structure, and the porosity, pure water flux, mean effective pore size and breaking strength of these prepared membranes increased with increasing the temperature of the coagulation bath. Highlights: The dope solutions with the addition of HBPEs were successfully prepared. The properties of these dope solutions were measured. Porous hollow fiber membranes were successfully prepared via RTIPS. Through the RTIPS process, these membranes exhibited unique properties. With the addition of HBPE, these membranes exhibited unique properties.